Indiana Jones and the kingdom of the crystal skull - Spielberg, Steven, 1946-; Marshall, Frank; Koepp, David; Lucas, George, 1944-; Ford, Harrison, 1942-; Blanchett, Cate, 1969-; Allen, Karen, 1951-; Winstone, Ray, 1957-; Hurt, John, 1940-2017; Broadbent, Jim; LaBeouf, Shia, 1986-; Copyright Collection (Library of Congress) (United States : Paramount Pictures Corporation, 2008)
Famed archaeologist/adventurer Dr. Henry "Indiana" Jones is called back into action when he becomes entangled in a Soviet plot to uncover the secret behind mysterious artifacts known as the crystal skulls.
Copyright Claimant: Lucasfilm Ltd. Pre-existing Material: Based on characters created by George Lucas and Philip Kaufman. Some previously published musical compositions, sound recordings, film and video clips, posters, and artwork. Date of Creation: 2008; Date of Publication: 2008-05-22; Registration Number / Date: PA0001597330 / 2008-05-22.
Summary from Internet movie database.
Not viewed.
Sources used: Copyright staff catalog online; Variety, May 26, 2008; Internet movie database, viewed Aug. 16, 2008.
Executive producers, George Lucas, Kathleen Kennedy ; story, George Lucas, Jeff Nathanson ; camera, Janusz Kaminski ; editor, Michael Kahn ; music, John Williams ; production designer, Guy Hendrix Dyas ; sound, Ronald Judkins.
Harrison Ford, Cate Blanchett, Karen Allen, Ray Winstone, John Hurt, Jim Broadbent, Shia LaBeouf.
Keywords: Fantasy films; Fiction films; Science fiction films